VIIIth International Conference of the Balkan Association of Roman Law and Roman Legal Tradition Societas pro Iure Romano Cres, 5-6 October 2023 - Sadowski, Piotr (The Opole Studies in Administration and Law, 2024)
Sprawozdanie